Diagnóstico do potencial da atividade de pesca esportiva no Rio Cuieiras, na área da Reserva de Desenvolvimento Sustentável – RDS Puranga Conquista - Oliveira Junior, Flávio Ruben Paes de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Sport fishing is practiced by people all over the world, becoming an important economic and social activity in Brazil since the 1990s. In the State of Amazonas, the Cuieiras River, which includes part of the limits of the Puranga Conquista Sustainable Development Reserve, harbors populations of the peacock bass (Cichla spp.) and has attracted urban, amateur and sports fishermen, especially on weekends. However, uncontrolled fishing in the reserve in the last few years resulted in conflicts for fishing areas between local communities and sport fishermen. Therefore, this study intends to diagnose the potential of the Cuieiras River in the RDS Puranga Conquista to the development of sport fishing activities, as well as to propose a strict protocol to carry out the activity in the reserve. For this, experimental sport fishing was carried out in the Cuieiras River employing a balanced sampling design and with strict control of the fishing effort, to compare the yeld of three fish habitat types: beaches, banks, and emergent dead trunks. The average fishing yield in relation to the number of pitches was relatively low, with actions (attacks to the baits, with or without captures) occurring in less than 5% of the pitches. There were no differences in catches among the three habitat types. The peacock basses Cichla orinocensis and C. temensis were the most frequently caught species, ranging in size from 30 to 40 cm in total length. The instantaneous mortality rate of the captured individuals was low (4.1%) and was mainly due to injuries to the branchial arches caused by the hooks. During the development of the field campaign, there were cases of irregular use of the RDS Puranga Conquista area for tourist visitation and sport fishing, with suspicion of a large quantity of peacock basses being slaughtered, which raises concern about the state of conservation of the local fish stocks in the reserve. An operational protocol is proposed based on a Matrix of Problems and Solutions, aiming to facilitate the implementation of sports fishing tourism in the reserve, in an environmentally sustainable and socially fair way.
Keywords: Pesca esportiva; Unidade de Conservação de uso direto; Manejo de recursos naturais; Tucunaré